An Overview of Rhodoliths: Ecological Importance and Conservation Emergency - Dimítri de Araújo Costa; Marina Dolbeth; Martin Lindsey Christoffersen; Pamela Tatiana Zúñiga-Upegui; Márcia Venâncio; Reinaldo Farias Paiva de Lucena (Life, 2023)
Red calcareous algae create bio-aggregations ecosystems constituted by carbonate calcium, with two main morphotypes: geniculate and non-geniculate structures (rhodoliths may form bio-encrustations on hard substrata or unattached nodules). This study presents a bibliographic review of the order Corallinales (specifically, rhodoliths), highlighting on morphology, ecology, diversity, related organisms, major anthropogenic influences on climate change and current conservation initiatives. These habitats are often widespread geographically and bathymetrically, occurring in the photic zone from the intertidal area to depths of 270 m. Due to its diverse morphology, this group offers a special biogenic environment that is favourable to epiphyte algae and a number of marine invertebrates. They also include holobiont microbiota made up of tiny eukaryotes, bacteria and viruses. The morphology of red calcareous algae and outside environmental conditions are thought to be the key forces regulating faunistic communities in algae reefs. The impacts of climate change, particularly those related to acidification, might substantially jeopardise the survival of the Corallinales. Despite the significance of these ecosystems, there are a number of anthropogenic stresses on them. Since there have been few attempts to conserve them, programs aimed at their conservation and management need to closely monitor their habitats, research the communities they are linked with and assess the effects they have on the environment.